2018
DOI: 10.1039/c7ta10802h
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Ag-anchored N-doped graphene/carbon foam for the selective electrochemical reduction of carbon dioxide to ethanol

Abstract: 3D macroporous hierarchical Ag-G-NCF can efficiently convert CO2 to ethanol with a low overpotential, high faradaic efficiency and high selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(69 citation statements)
references
References 28 publications
1
68
0
Order By: Relevance
“…Synthesis of NiSA‐NGA and NGA : GO was prepared from natural flake graphite powder following a modified Hummer's method . NiSA‐NGA catalysts were synthesized using impregnation‐pyrolysis method . In a typical process, a certain amount of 3 mg mL −1 NiCl 2 ·6H 2 O and 15 µL of 30% H 2 O 2 were added to 10 mL of 2 mg mL −1 GO suspension under gentle agitation for 1 h. After that, a patch of MF was immersed in the above mixed suspension, and then dried in an oven.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of NiSA‐NGA and NGA : GO was prepared from natural flake graphite powder following a modified Hummer's method . NiSA‐NGA catalysts were synthesized using impregnation‐pyrolysis method . In a typical process, a certain amount of 3 mg mL −1 NiCl 2 ·6H 2 O and 15 µL of 30% H 2 O 2 were added to 10 mL of 2 mg mL −1 GO suspension under gentle agitation for 1 h. After that, a patch of MF was immersed in the above mixed suspension, and then dried in an oven.…”
Section: Methodsmentioning
confidence: 99%
“…Porous Pd films produced acetate of 5 % FE though with 50 % formate and 15 % methanol . Ag‐anchored N‐doped graphene/carbon foam catalyzed ethanol production with 82 % FE . According to these works, limiting intermediates diffusion seems an effective strategy for noble metal based catalysts producing C2+ products.…”
Section: Recent Progress Towards Practical Electrochemical Co2 Splittingmentioning
confidence: 99%
“…Recently, Kanan group reported oxide‐derived nanocrystalline Cu can efficiently convert CO 2 into a variety of oxygenates, which is considered to be facilitated by high density of grain boundaries on the catalyst surface . Interestingly, several recent reports have shown that C2 molecules could be generated with high selectivity by using heteroatom doped carbon‐based composites other than Cu‐based materials . In South Korea, as described in Scheme , electrochemical CO 2 reduction to multi‐carbon products using Cu‐based materials and others have not been paid much attention until very recently.…”
Section: Research Trends In Electrochemical Reduction Of Co2 At the Ementioning
confidence: 99%